Research on New Media Marketing of Credit Card Business - Zou, Zhihui; Cheng-Jui, Tseng (International Journal of Multidisciplinary in Management and Tourism, 2022)
This article has three research objectives: To examine the significance of the credit card business in the Guangzhou branch of ICBC. To assess the relationship between new media marketing and credit-card business profitability. To examine the nature of new media marketing strategies that can effectively promote credit-card business development. The sample was drawn from the population of consumers of credit cards in the Guangzhou province of China. They were selected through face-to-face interceptions in various locations, such as shopping malls and various destination sites in Guangzhou cities. Analysis of data by simple descriptive statistics and qualitative understanding. The research results were found as follows; There is a strategic need to improve the product and service quality of the credit-card businesses in Guangzhou, relax the credit limit, and expand customer channels. An emphasis on the creative use of new media marketing to further develop the credit-card business and improve profitability, by paying attention to the detailed disposition and constantly optimizing the process using new media marketing platforms.